Ranking Methodology for Evaluating Region-Wise COVID-19 Testing Performance in India - Kaur, Jasmine; Kaur, Jasleen; Singh, Harpreet (Frontiers in Public Health, 2022)
For containment of COVID-19, most countries are following the isolate, test, treat and trace approach. Following the approach, India scaled up COVID-19 testing from about 5,000 tests per day at the end of March 2020 to more than 1 M tests per day in September 2020. Testing scale-up has seen a huge variation across states and union territories (UTs) with respect to growth rates, testing strategies, testing infrastructure, and deployment of various kit types (RT-PCR, Antigen, CBNAAT, etc). To understand the gaps in testing and prioritize appropriate interventions, it is important for national stakeholders to evaluate and rank states/UTs based on their testing performance. Indicators like total samples tested, total samples positive, tests per million, and positives per million are currently being used by epidemiologists and researchers for comparing the performance of various regions. This article proposes a robust ranking methodology to rank the states/UTs in India based on a comprehensive scoring developed by combining multiple variables for evaluating the testing performance of states/UTs. Since RT-PCR testing is considered the gold standard for COVID-19 testing, the composite score for testing performance in this article is defined by the ability of states/UTs to successfully deploy RT-PCR testing and reduce its positivity over time. Evaluating region-wise ranking can enable the identification of areas requiring immediate attention in poorly performing regions, thus channelizing efforts and resources in the right direction.